2020
DOI: 10.1111/ppl.13260
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cell cycle progression and chromatin dynamic as tolerance mechanisms to salinity and drought stress in maize

Abstract: Salinity and drought are the major abiotic stresses that disturb several aspects of maize plants growth at the cellular level, one of these aspects is cell cycle machinery.In our study, we dissected the molecular alterations and downstream effectors of salinity and drought stress on cell cycle regulation and chromatin remodeling. Effects of salinity and drought stress were determined on maize seedlings using 200 mM NaCl (induced salinity stress), and 250 mM mannitol (induced drought stress) treatments, then ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 58 publications
1
26
0
Order By: Relevance
“…Several studies have shown that salt stress can affect multiple morphological, physiological, biochemical, and molecular aspects of plants [6,17,40]. In this study, we observed that exposing plants to salt stress inhibited plant growth parameters, including plant height, fresh weight, dry weight, and leaf area as compared to the unstressed plants (Figure 1).…”
Section: Discussionmentioning
confidence: 51%
“…Several studies have shown that salt stress can affect multiple morphological, physiological, biochemical, and molecular aspects of plants [6,17,40]. In this study, we observed that exposing plants to salt stress inhibited plant growth parameters, including plant height, fresh weight, dry weight, and leaf area as compared to the unstressed plants (Figure 1).…”
Section: Discussionmentioning
confidence: 51%
“…4a and b). Overproduction of ROS under abiotic stress usually leads to an oxidative damage to the cellular components, leading to membrane lipid peroxidation and cell membrane destruction (Kamal et al, 2021;Sasi et al, 2021;Sun et al, 2017). The MDA and Evans blue uptake are considered as key indicators of lipid peroxidation and integrity of the plasma membrane in plants to re ect the degree of membrane damage (Sun et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Under drought conditions, rice plants also showed a reduction in their growth with decreased height and shoot dry mass and a smaller number of leaves [ 171 ]. Under salt and water stress, the levels of CYCB1 , CYCA1 , and CDKA/CDKB in maize are drastically reduced [ 172 ], indicating an interruption in the cell cycle checking process performed by these two groups of cyclins and by the association with CDKA and CDKB [ 173 ] ( Figure 2 A).…”
Section: Cell Cycle and Plant Plasticity As Adaptive Responsesmentioning
confidence: 99%